Avaliação da relação da qualidade do ar com a pandemia do novo coronavírus e diagnóstico ambiental do material particulado no município de João Pessoa/PB - Medeiros, Ana Mayara Andriola (2022)
Air pollution is one of the most important problems in the world today due to the numerous harmful effects that can affect human health and the environment, among the pollutants, particulate matter (PM) is one of the main ones found in urban areas. In addition, another major problem in the world today is the new Coronavirus pandemic, which continues to this day. Therefore, the general objective of the study is: The first chapter is a literature review on the close relationship between air quality and contamination by Coronavirus (SARS-CoV-2). The virus can be airbone by aerosols and remain active for a certain time; it was also observed that there is a correlation between the reduction of air pollution and the decrease in the rate of infection and lethality of Covid-19 cases, moreover, the effects of air pollutants on the lungs interfere with the prognosis and involution of patients’ conditions. Some climate indicators are also significantly correlated with the disease. The second chapter is about the implications of restrictive measures of social isolation on particulate matter emissions before and during the pandemic, for the years 2019 and 2020. In this chapter it is possible to observe that the restrictions imposed by State Decree No. 4606- R/ 2020, influenced the concentration of PM10 in the city of Vitória (ES), which had a 23% reduction in PM10 levels; already to the city of Vila Velha (ES) there was no considerable variation in the concentration of PM10. The third chapter addresses the concentration of particulate matter in the city of João Pessoa-PB/Brazil, through the monitoring of PM10 in two distinct points of the city. For the first collection method, it was possible to conclude that in Point 1 the PM10 concentration is influenced by vehicle traffic and the wind direction, the further east the wind blows the higher the particulate concentration, furthermore for this wind position the concentration of PM10 violated the limits of the Resolution CONAMA N 491/2018. For Point 2, the concentration was in accordance with the Resolution cited. In the second method of collection, it was found that in Point 1 the particles are retained in the atmosphere and accumulate of throughout the day. For Point 2 there were no inferences.